The Students’ Strategies Used to Overcome the Problems in the Paragraph Writing Course - Sakkir, Rini Isnaeni; Muh. Tahir; Sofyan, Ryan Rayhana (EduLine: Journal of Education and Learning Innovation, 2025)
This study investigates the strategies employed by second-year students at Universitas Negeri Makassar to overcome challenges in the Paragraph Writing course. The research identifies key strategies such as personal approaches to practice, utilizing additional references, seeking help from peers and lecturers, planning and outlining before writing, and improving vocabulary and grammar. These strategies provide valuable insights into how students navigate writing difficulties and improve their writing skills. The findings can inform teaching practices, offering practical suggestions for enhancing writing instruction in English as a Foreign Language (EFL) contexts.